Analysis of risk factors of feeding intolerance in ICU patients with enteral nutrition (ICU肠内营养患者喂养不耐受的危险因素分析) - LI Peiyao (李佩瑶); WANG Yue (王玥); ZHANG Yang (张洋); ZHANG Jinjuan (张金娟); JIA Dan (贾丹) (中西医结合护理)
Objective To investigate the risk factors of feeding intolerance in ICU patients with enteral nutrition. Methods Totally 504 ICU patients who received enteral nutrition support were selected and divided into tolerance group (n=331) and intolerance group (n=173) according to the symptoms of feeding intolerance. The general data, tolerance, enteral nutrition preparations, clinical treatment and drug application of the two groups were compared. Binary Logistic regression analysis was used to analyze the risk factors of feeding intolerance. Results The daily dosage of enteral nutrition preparations (OR=1. 007), time to start enteral nutrition (OR=7. 361), mechanical ventilation (OR=25. 643), vasoactive drugs (OR=19. 049), antibiotics (OR=23. 267), length of hospitalization (OR=1. 522), and acid-inhibiting drugs (OR=0. 149) were risk factors of feeding intolerance, and probiotics(OR=0. 016)was a protective factor of feeding intolerance. Conclusion The feeding intolerance of ICU patients is dependent on many factors, and targeted nursing measures should be carried out to improve the nutrition status of ICU patients. (目的 探讨ICU患者肠内营养发生喂养不耐受的危险因素。方法 选取2023年1月—10月行肠内营养支持的504例ICU患者, 根据有无喂养不耐受症状分为耐受组(n=331)与不耐受组(n=173), 比较两组患者一般资料、耐受性情况、肠内营养制剂、临床治疗、药物应用等情况, 采用二分类 Logistic 回归分析探讨ICU患者喂养不耐受的危险因素。结果 制剂日用量(OR=1. 007)、开始肠内营养时间(OR=7. 361)、机械通气(OR=25. 643)、血管活性药(OR=19. 049)、抗菌药(OR=23. 267)、住院天数(OR=1. 522)、抑酸药(OR=0. 149)是ICU患者发生喂养不耐受的危险因素; 益生菌(OR=0. 016)是ICU患者发生喂养不耐受的保护因素。结论 ICU患者发生喂养不耐受和多种因素有关, 应实施针对性干预措施, 积极改善ICU患者营养状况。)